AN ANALYSIS OF STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT - Kurniawan, Robi; Kurniawan, Reza Wahyu (GoAcademica CRP, 2025)
This study aims to analyze the reading comprehension of narrative texts among ninth-grade students at MTs Negeri 3 Kampar. According to the curriculum established by the Indonesian government, students are expected to comprehend various elements of narrative texts, including their generic structures and language features. This research employed a descriptive quantitative method, with data collected through a multiple-choice test consisting of 24 items. The test measured students’ abilities to identify factual information, main ideas, vocabulary meaning, references, inferences, orientations, complications, and resolutions. The findings reveal that students’ average reading comprehension score falls within the “Good” category, with a mean score of 80. Approximately 55% of students demonstrated strong ability in identifying factual information, and 64% were able to determine the main idea. However, some students experienced difficulties, particularly in identifying references and making inferences. These findings underscore the need for more effective instructional strategies and interventions to enhance students’ comprehension skills. It is expected that this research will offer valuable insights for educators in improving students’ understanding of narrative texts.